Anti-Alphaviral Alkaloids: Focus on Some Isoquinolines, Indoles and Quinolizidines - Anne-Laure Sandenon Seteyen; Emmanuelle Girard-Valenciennes; Axelle Septembre-Malaterre; Philippe Gasque; Pascale Guiraud; Jimmy Sélambarom (Molecules, 2022)
The discovery and the development of safe and efficient therapeutics against arthritogenic alphaviruses (e.g., chikungunya virus) remain a continuous challenge. Alkaloids are structurally diverse and naturally occurring compounds in plants, with a wide range of biological activities including beneficial effects against prominent pathogenic viruses and inflammation. In this short review, we discuss the effects of some alkaloids of three biologically relevant structural classes (isoquinolines, indoles and quinolizidines). Based on various experimental models (viral infections and chronic diseases), we highlight the immunomodulatory effects of these alkaloids. The data established the capacity of these alkaloids to interfere in host antiviral and inflammatory responses through key components (antiviral interferon response, ROS production, inflammatory signaling pathways and pro- and anti-inflammatory cytokines production) also involved in alphavirus infection and resulting inflammation. Thus, these data may provide a convincing perspective of research for the use of alkaloids as immunomodulators against arthritogenic alphavirus infection and induced inflammation.